Math, asked by suzukililly396, 9 months ago

\begin{cases}a(1)=\dfrac{5}{3}\\\\ a(n)=a(n-1)\cdot (-9) \end{cases}
What is the 3rd term in the sequence

Answers

Answered by Imblank
1

Answer:

135

a(3) = a(3-1).(-9) = a(2).(-9) = -15.-9 = 135

a(2) = a(2-1).(-9) = a(1).(-9) = 5/3.-9 = -15

Read my bio once

Answered by ompirkashsingh893349
1

Answer:

Hey mate, here is your Answer:)

Mark me as BRAINLIST!!

Step-by-step explanation:

135

135a(3) = a(3-1).(-9) = a(2).(-9) = -15.-9 = 135

Similar questions